Unlocking multimodal PET-MR synergies for geoscience. (August 2020) - Brattekås, B.; Gauteplass, J.; Brekke, N.; Fernø, M.A.; Ersland, G.
Highlights: Multimodal Imaging by PET-MR demonstrated for water flow in porous media. 4D fluid flow mapping by PET-MR with high reproducibility between modalities. Excellent correlation of fluid distribution on core and sub-core scales. Opportunity to track three fluid phases in opaque systems. Abstract: The recent combination of positron emission tomography (PET) and magnetic resonance (MR) imaging modalities in one clinical diagnostic tool represents a scientific advancement with high potential impact in geoscientific research; by enabling simultaneous and explicit quantification of up to three distinct fluids in the same porous system. Decoupled information from PET-MR imaging was used here, for the first time, to quantify spatial and temporal porous media fluid flow. Three-dimensional fluid distribution was quantified simultaneously and independently by each imaging modality, and fluid phases were correlated with high reproducibility between modalities and repetitive fluid injections. Graphical abstract: Image, graphical abstract